New fluorescent imidazo[1, 2-a]pyridine-BODIPY chromophores: Experimental and theoretical approaches, and cell imaging exploration. (July 2017) - Wu, Yuxiao; Yuan, Wei; Ji, Heyi; Qin, Yaru; Zhang, Jin; Li, Hongkun; Li, Yahong; Wang, Yong; Sun, Yufang; Liu, Wei
Abstract: Based on imidazo[1, 2- a ]pyridine derivatives, a series of mononuclear and binuclear fluorine-boron complexes1a, b, 4a, b, and5a, b have been designed and synthesized. X-ray crystal structures for single boron-core complexes1b, 4a, 4b, and dual boron-core imidazo[1, 2- a ]pyridine-BODIPY dyad5b were obtained, and intermolecular CH⋯F interactions were observed in their solid state. High absorption coefficients, strong emissions, and high photostabilities have been demonstrated for these boron complexes. DFT and TD-DFT studies reveal efficient electronic interactions between the imidazo[1, 2- a ]pyridine moiety and BODIPY plane for dyads4a, b, and5a, b . Cell imaging of4a was tested to show good cellular uptake ability. Graphical abstract: Highlights: We synthesize two novel boron complexes based on imidazo[1, 2- a ]pyridine and four imidazo[1, 2- a ]pyridine-BODIPY dyads. DFT and TDDFT calculations have provided insight into interpreting the electronic properties. Luminescent emissions were investigated, and one imidazo[1, 2- a ]pyridine-BODIPY dyad4a can be used as effective cell imaging regent.